Automated, 3‐D and Sub‐Micron Accurate Ablation‐Volume Determination by Inverse Molding and X‐Ray Computed Tomography. Issue 20 (6th May 2022) - Monserrat Lopez, Diego; Grimaudo, Valentine; Prone, Giulia; Flisch, Alexander; Riedo, Andreas; Zboray, Robert; Lüthi, Thomas; Mayor, Marcel; Fussenegger, Martin; Broekmann, Peter; Wurz, Peter; Lörtscher, Emanuel
Abstract: Ablation of materials in combination with element‐specific analysis of the matter released is a widely used method to accurately determine a material's chemical composition. Among other methods, repetitive ablation using femto‐second pulsed laser systems provides excellent spatial resolution through its incremental removal of nanometer thick layers. The method can be combined with high‐resolution mass spectrometry, for example, laser ablation ionization mass spectrometry, to simultaneously analyze chemically the material released. With increasing depth of the volume ablated, however, secondary effects start to play an important role and the ablation geometry deviates substantially from the desired cylindrical shape. Consequently, primarily conical but sometimes even more complex, rather than cylindrical, craters are created. Their dimensions need to be analyzed to enable a direct correlation with the element‐specific analytical signals. Here, a post‐ablation analysis method is presented that combines generic polydimethylsiloxane‐based molding of craters with the volumetric reconstruction of the crater's inverse using X‐ray computed tomography. Automated analysis yields the full, sub‐micron accurate anatomy of the craters, thereby a scalable and generic method to better understand the fundamentals underlying ablation processes applicable to a wide range of materials. Furthermore, it may serve toward a more accurate determination of heterogeneous material's composition for a variety of applications without requiring time‐ and labor‐intensive analyses of individual craters. Abstract : Laser ablation of materials combined with element‐specific analytics enables a direct correlation between the volumes ablated and its elemental composition. By crater molding by polydimethylsiloxane and X‐ray computed tomography thereof, a digital surface topology is created with sub‐micron accuracy. Large arrays comprising systematic ablation parameters variations enable volume, depth, and ablation rate to be determined in an efficient manner.